2010
DOI: 10.1056/nejmoa1001278
|View full text |Cite
|
Sign up to set email alerts
|

Step-up Therapy for Children with Uncontrolled Asthma Receiving Inhaled Corticosteroids

Abstract: BACKGROUND For children who have uncontrolled asthma despite the use of low-dose inhaled corticosteroids (ICS), evidence to guide step-up therapy is lacking. METHODS We randomly assigned 182 children (6 to 17 years of age), who had uncontrolled asthma while receiving 100 µg of fluticasone twice daily, to receive each of three blinded step-up therapies in random order for 16 weeks: 250 µg of fluticasone twice daily (ICS step-up), 100 µg of fluticasone plus 50 µg of a long-acting beta-agonist twice daily (LABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
253
0
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(268 citation statements)
references
References 21 publications
2
253
0
13
Order By: Relevance
“…Moreover, some patients who do not achieve optimal control of symptoms show improvement in some features of clinical control reaching a more satisfactory or tolerable state, even though their composite control scores (such as the ACQ-7 or ACT) remain at an uncontrolled level [185,197]. In poorly controlled paediatric asthma on low-dose ICS, addition of LABAs were the most effective add-on therapy to ICS compared with doubling the dose of ICS or to the addition of montelukast, but there was marked variability in the treatment response highlighting the need to regularly monitor and appropriately adjust each child's asthma therapy [198]. No such study has yet been reported in severe paediatric asthma.…”
Section: Inhaled and Oral Corticosteroid Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some patients who do not achieve optimal control of symptoms show improvement in some features of clinical control reaching a more satisfactory or tolerable state, even though their composite control scores (such as the ACQ-7 or ACT) remain at an uncontrolled level [185,197]. In poorly controlled paediatric asthma on low-dose ICS, addition of LABAs were the most effective add-on therapy to ICS compared with doubling the dose of ICS or to the addition of montelukast, but there was marked variability in the treatment response highlighting the need to regularly monitor and appropriately adjust each child's asthma therapy [198]. No such study has yet been reported in severe paediatric asthma.…”
Section: Inhaled and Oral Corticosteroid Therapymentioning
confidence: 99%
“…Montelukast is not as effective as LABAs when added to ICS therapy in preventing exacerbations requiring systemic corticosteroids or improving symptoms in moderate asthma [4,198]. Addition of a leukotriene receptor antagonist or synthesis inhibitor has shown some efficacy on lung function when added to ICS in three studies of adults with moderate-to-severe asthma who were not taking LABAs.…”
Section: Leukotriene Pathway Modifiersmentioning
confidence: 99%
“…Response variability will likely exist among obese asthmatics, as it does among lean asthmatics. 157 Because of the flat dose-response curve and steroid resistance seen among obese asthmatics, initial step-up therapy for obese asthmatics with poor control should include ICS plus montelukast. However, regardless of the step-up therapy chosen, close patient follow-up is critically important to reassess and reiterate proper inhaler techniques, weight control, low-fat diet, daily exercise, and monitoring of asthma symptoms and medication side-effects.…”
Section: Obesity Nutrition and Asthma In Childrenmentioning
confidence: 99%
“…Para esta sugerencia se toman en cuenta los beneficios reportados en dos estudios aleatorios en niños con la combinación CEI + LABA: reducción en las crisis asmáticas, mejoría en la función pulmonar, reducción en el uso de corticosteroides sistémicos 45,46 y los posibles efectos negativos sobre la estatura que se han documentado con dosis medias o altas de CEI en niños. Dada la heterogeneidad en la respuesta individual, sugerimos probar las alternativas en caso de no obtener un efecto benéfico con CEI + LABA a las 4-6 semanas del manejo.…”
Section: Rescateunclassified